John Witherspoon and the Rhetoric of Reputation - Bourbouhakis, Emmanuel C. (Theology today, 2024)
The controversy surrounding the statue of John Witherspoon on Princeton's campus has revolved largely around his contentious stance on the gradual abolition of slavery and his presumed ownership of at least two slaves for some indeterminate period. This article is intended to shift the focus to Witherspoon's pedagogical legacy as the more appropriate measure of his place on campus.